(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Professional success is defined as the sum of people’s real and perceived positive achievements as a result of their work experiences. However, there is no absolute measure of achievement after completing the college level. Problems may occur in such situations, such as finding job chances to put one’s expertise to use. The researchers have found that the graduates prioritized their needs before wants and avoided financial obligations. They also enjoyed their workloads and strongly agreed that employees should be sent to training for development. In terms of career fulfillment, the respondents believed that their personality type, upbringing, and work-related values shaped their professional goals. Lastly, they rated positive mastery experiences as important for developing their self-sufficiency. The researchers propose that BSAIS graduates should work on developing their financial literacy, time management skills, career planning, and self- confidence to become self-sufficient learners. Additionally, the researchers suggest that the BSAIS faculty should support the graduates in enhancing their financial literacy and engage them in career planning to achieve their desired professional goals. In conclusion, this study provides valuable insights into the factors that influence the professional success of BSAIS graduates. The findings highlight the importance of financial literacy, career planning, and self-sufficiency for achieving success in the accounting and information system field. The results of this study could be used by BSAIS graduates and faculty to develop personal development plans and strategies that will help them achieve their professional goals. Overall, this study contributes to the growing body of knowledge on the factors that influence professional success and can be used to inform future research in this area.